Seafood provides significant health benefits for men - McManus, Alexandra; Fielder, Lynda; Newton, Wendy (Elsevier, 2011)
Evidence supports the regular consumption of Omega-3 polyunsaturated fatty acids found (Omega 3s) with positive effects to men?s health. The best source of these essential fatty acids are seafood, particularly oily fish. This article summarises evidence pertaining to the benefits associated with regular dietary intake of fish on men?s health.Methods: An extensive review of international academic libraries, databases and published literature was conducted. Quality assessment ratings were applied and thematic classifications based on major health issues relevant to men constructed.Results: A total of 168 articles from peer reviewed journals were identified with 60 studies providing moderate to high level evidence of an association between the consumption of Omega 3s and health benefit for men. The majority of the studies showed a positive link between the intake of Omega 3s and the prevention and management of chronic disease in men. Evidence also shows a reduced risk of prostate cancer and lower lung cancer mortality in men who consume a high seafood diets. Conclusion: There is conclusive evidence of an association between the dietary intake of Omega 3s and health benefits for men. However, men are less likely to consume fish when compared to red or white meats. Health promotion interventions should consider: the attitudes of men toward food and the impact of these attitudes on food choices; the association between seafood and other protein sources within the male psyche; and the role that particular foods play for males in social situations.